1994
DOI: 10.1038/371261a0
|View full text |Cite
|
Sign up to set email alerts
|

Location of a folding protein and shape changes in GroEL–GroES complexes imaged by cryo-electron microscopy

Abstract: Protein folding mediated by the molecular chaperone GroEL occurs by its binding to non-native polypeptide substrates and is driven by ATP hydrolysis. Both of these processes are influenced by the reversible association of the co-protein, GroES (refs 2-4). GroEL and other chaperonin 60 molecules are large, cylindrical oligomers consisting of two stacked heptameric rings of subunits; each ring forms a cage-like structure thought to bind polypeptides in a central cavity. Chaperonins play a passive role in folding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
265
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 340 publications
(284 citation statements)
references
References 26 publications
18
265
1
Order By: Relevance
“…most EM images of GroES/GroEL complexes, the GroES appeared to be a domed cap at the end of GroEL, indicating that the surface of GroES facing the GroEL lumen is concave [8,17,19]. Therefore, the observed GroES surface with the AFM should be the surface facing away from the GroEL.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…most EM images of GroES/GroEL complexes, the GroES appeared to be a domed cap at the end of GroEL, indicating that the surface of GroES facing the GroEL lumen is concave [8,17,19]. Therefore, the observed GroES surface with the AFM should be the surface facing away from the GroEL.…”
Section: Resultsmentioning
confidence: 97%
“…Each monomer of GroES has a nominal molecular weight of 10 kDa [2], and the GroES is normally found in an oligomeric configuration of seven subunits [2,13]. Although no specific functions have been identified with the GroES heptamer alone, it has been firmly established with both electron microscopy (EM) and biochemical methods that, in the presence of ATP or ADP, the GroES heptamer can form a stable complex with the GroEL tetradecamer [5,8,[18][19][20]. Upon the binding of GroES, the rate of ATP hydrolysis of GroEL is strongly affected [4,6,7,9,12,21], but the mechanism has not been well understood [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion that the GroES mobile loops at least in part bind to and compete for the same surface of GroEL as polypeptide is supported both by observations in electron microscopy of the site of contact (Chen et al, 1994;Roseman et al, 1996) and by mutational findings that the same channel-facing residues critical for polypeptide binding (Fig. 1B) are also critical for binding GroES .…”
Section: A Architecture Of the Chaperoninsmentioning
confidence: 85%
“…Electron microscopy studies have shown that non-native polypeptides are bound in these channel openings (Langer et al, 1992;Braig et al, 1993;Chen et al, 1994;Ishii et al, 1994). Because the amino acids forming the walls of the channel are hydrophobic in character (Fig.…”
Section: A Architecture Of the Chaperoninsmentioning
confidence: 99%
See 1 more Smart Citation